The perception of UiTMCS students toward resident and non resident accommodation / Mazlan Sidi & Aziz Jadid - Sidi, Mazlan; Jadid, Aziz (2005)
Our research is to know how many students living in outside and inside the campus also what their reason living in campus and outside. The source of our information is student from part 2 until 7 from all courses like Diploma in Accounting, Diploma Public Administration, Diploma Business Study, Diploma Civil Engineering and many again. The technique we use to find the information through questionnaire distribute to 50 students in UiTM campus Samarahan Sarawak.